2014
DOI: 10.1016/j.meegid.2013.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus: Determinants of human carriage

Abstract: Staphylococcus aureus is a common human commensal but carriage varies between e.g. geographic location, age, gender, ethnicity and body niche. The nares, throat and perineum are the most prevalent sites for carriage in the general adult population. Other sites of the skin and the intestine are also frequently colonised. Thus, a successful establishment is dependent on multiple factors. This review describes results from observational studies of S. aureus carriage and the influence bacterial, host and environme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
189
5
10

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(215 citation statements)
references
References 152 publications
11
189
5
10
Order By: Relevance
“…Two samples were collected over a 6-week period from each subject and grouped by carriage state into noncolonizers (both samples S. aureus negative), intermittent colonizers (one sample positive/one sample negative), and long-term colonizers (both samples positive). Since the sampling occurred only over a 6-week period and only two samples were obtained, we could not designate these long-term colonizers as persistently colonized, which are defined as S. aureus culture-positive nasal swabs collected on 5 to 10 separate occasions during a 6-month period, and subjects are labeled as persistent carriers if Ͼ80% of the cultures are positive (36)(37)(38). In our studies with S. aureus, we found that 68% of patients were noncolonizers, 17% were intermittent colonizers, and 15% were long-term colonizers (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Two samples were collected over a 6-week period from each subject and grouped by carriage state into noncolonizers (both samples S. aureus negative), intermittent colonizers (one sample positive/one sample negative), and long-term colonizers (both samples positive). Since the sampling occurred only over a 6-week period and only two samples were obtained, we could not designate these long-term colonizers as persistently colonized, which are defined as S. aureus culture-positive nasal swabs collected on 5 to 10 separate occasions during a 6-month period, and subjects are labeled as persistent carriers if Ͼ80% of the cultures are positive (36)(37)(38). In our studies with S. aureus, we found that 68% of patients were noncolonizers, 17% were intermittent colonizers, and 15% were long-term colonizers (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Interactions between commensal bacteria and the ability of Staphylococcus aureus to colonise the nasal cavity have been shown and provide evidence to support the concept of colonization resistance. 10 The study was challenged by being of a pragmatic design being undertaken in a clinical setting. The patients were heterogeneous with regard their underlying conditions and antibiotic regimens.…”
Section: Discussionmentioning
confidence: 99%
“…aureus are Gram-positive cocci with the potential to cause serious infections including bacteremia, endocarditis, and pneumonia, as well as skin and soft tissue infections ranging from impetigo to necrotizing fasciitis. More than one-third of the general population is asymptomatically colonized with S. aureus on either a transient or persistent basis, most frequently in the nose, throat, and perineum [12][13][14]. These colonizers are frequently the source of host staphylococcal infections, and patients with positive nasal swabs for S. aureus are known to be at high risk of nosocomial and surgical site infections [15].…”
Section: Introductionmentioning
confidence: 99%
“…Smokers are more likely than nonsmokers to be colonized with S. aureus, defined as >500 colony forming units (CFU) detected, with rates of colonization increasing with duration and frequency of smoking [14,16,17]. Smokers have an increased incidence of invasive staphylococcal infections than nonsmokers and have higher mortality as well [17][18][19].…”
Section: Introductionmentioning
confidence: 99%